Pendidikan Berbasis Pesantren - Sudadi (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2019)
This research originates from the general belief that most generations of Indonesia that are predominantly Muslims attend public schools and not madrasas, whereas the Islamic Religious Education (PAI) taught to Muslim students in public schools is only dogmatic Islamic teachings.As a result, many Muslim students from public schools have poor understanding of their religion and do not understand it perfectly (kaffah). In fact,cognitive aspects are only a priority in discussion. To practice and respect the beliefs of Islam (Aqeedah) and morals, these two things are far from expectations. Therefore, Islamic education in public schools from elementary school to secondary school must employ development, modification, innovation and additional learning programs so that the integral goal of Islamic education can be achieved. A more optimal learning system can be carried out by applying wider Islamic educations in public schools. The pesantren (Islamic Boarding School)-Based School Program launched in public schools is one of the programs as an effort to create students with moral character. It means that in the context of Islam religion it can be called the morality of karimah. The question depends on the implementation and effectiveness of the pesantren-based education programs in public schools. This study also discusses the development and learning process of Islamic education in public schools that generally implement pesantren-based school programs. This study focuses on objects in the Ma’arif Vocational School which has implemented this program since 2013 in Kebumen Regency. This study aims to describe a pesantren-based school by outlining the planning, implementation and evaluation of pesantren-based Islamic religious education learning system programs. The analytical approach is naturalistic by conducting a comprehensive and descriptive discussion on the focus of research in an integrated education system, with methods of observation, interviews and documentation, followed by testing data validity through frequent interactions with primary sources, observing more diligently and conducting conduction triangulation tests. In addition, this study uses descriptive analysis, cross case analysis and comparative and inductive reasoning for processing, discussion and analysis of findings.